Phenomenology and Sociology - Luckmann, Thomas (Harmondsworth : Penguin Books, 1978)
MEAD (George Herbert), What Social Objects must Psychology Presuppose ?
PLESSNER (Helmuth), With Different Eyes
HUSSERL (Edmund), The Origin of Geometry
GURWITSCH (Aron), Galilean Physics in the Light of Husserl's Phenomenology
LBBE (Hermann), Positivism and Phenomenology : Mach and Husserl
SCHUTZ (Alfred), Phenomenology and the Social Sciences
MERLEAU-PONTY (Maurice), The Philosopher and Sociology
WAELHENS (Alphonse de), The Human Sciences, the Ontological Horizon and the Encounter
NATANSON (Maurice), Phenomenology as Rigorous Science
O'NEILL (John), Can Phenomenology be Critical ?
LUCKMANN (Thomas), Philosophy, Social Sciences and Everyday Life
SCHUTZ (Alfred), Some Structures on the Life World
LUCKMANN (Benita), The Small Life-Worlds of Modern Man
HOLZNER (Burkart), The Construction of Social Actors : An essay on social identities
BUCKNER (Taylor), Transformations of Social Reality in the Legal Process
KELLNER (Hansfried), On the Cognitive Significance of the System of Language in Communication
BERGER (Peter), The Problem of Multiple Realities : Alfred Schutz and Robert Musil
bibliogr.